Posterior aortopexy is the option - Abdullah Al-Shamrani; Ahmed Elwy (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Tracheomalacia is the abnormal collapse and flaccidity of the supporting tracheal cartilage, leading to a reduction in the caliber of the anterior-posterior airway. Tracheomalacia is common after cardiac compression or tracheoesophageal fistula. In the severe type, tracheomalacia may lead to significant morbidity, especially if encountered at a younger age or in a critical area, such as the distal part of the trachea. We report two cases that did not improve after initial cardiac surgery with persistent airway narrowing of more than 80%, requiring prolonged ventilatory support. Both cases were difficult to manage but eventually showed a significant improvement after posterior aortopexy, which helped to wean them off the ventilator and produced marked clinical and radiological improvement. Both cases had residual malacia that was clinically presented as persistent audible wheezing and recurrent chest exacerbation. The diagnostic and therapeutic options for both cases are discussed.